DINAMIKA PSIKOLOGIS SANTRI DALAM MENGHADAPI TEKANAN AKADEMIK MELALUI KESADARAN FITRAH: STUDI KASUS DI PPTQ ANNASUCHIYYAH KUDUS - Muhammad Abdullah Najih; Dzakiyatul Ummah; Adillah Shinta Al Azizati (Pascasarjana Universitas Al-Qolam Malang, 2026)
This study aims to examine the psychological dynamics of Islamic boarding school students in coping with academic pressure and to explore the role of awareness of fitrah as a spiritual approach to alleviating such pressure. The approach used in this study is descriptive qualitative research with a case study design. The research subjects consisted of ten students at PPTQ Annasuchiyyah Kudus, who were selected through purposive sampling. Data collection techniques included semi-structured interviews, participatory observation, and documentation. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, presentation, and verification. The results of the study indicate that the students experience academic stress stemming from the burden of memorization, school assignments, and a demanding pesantren schedule. However, awareness of fitrah—which encompasses an awareness of spiritual, intellectual, and physical potential—plays a crucial role in helping students balance their emotions, find meaning in life, and enhance their mental resilience. The conclusion of this study confirms that fostering an awareness of fitrah is an effective approach to helping students cope with academic stress; therefore, it is highly recommended that this approach be integrated into the character and spiritual development curriculum at Islamic boarding schools.